Levels of formation of anti-victim personality in athletes - Baturkina,G. V.; Budyakova, T. P. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify levels of anti-victim personality formation in athletes. Methodology and structure of the study. The study used the method of expert assessments. The experts were current and former athletes aged 18 to 55 years in the number of 50 people. The material of the study was specially selected cases, which recorded the facts of victimization of athletes. The study participants had to offer effective means to avoid victimization in such cases. Results and conclusions. The analysis of the proposed options for resolving victim situations allowed us to prove that by the nature of the methods used to get out of the conflict, we can distinguish five levels of formation of an anti-victim personality: standard, medium-normative, borderline, pre-victim and victim. However, in reality, only 4% of the study participants were able to suggest ways to respond to a conflict situation at the reference level. Basically, options were offered that correspond to the victim and pre-victim levels. Special training is required to form a higher-level anti-victim personality.